Hubungan Tingkat Pengetahuan Orang Tua dengan Perilaku Pencegahan Kekerasan Seksual pada Anak Usia Dini - Baiq Nurul Hidayati; Desi Opra Isnaini; Fitri Romadonika; Zuliardi Zuliardi; Marthilda Suprayitna (STIKes YARSI Pontianak, 2026)
Background: Cases of sexual violence against children in Indonesia continue to increase, so early sexual education by parents is important as a preventive measure. However, many parents still consider the discussion of sexual education as taboo Objective: To deterrmine the relationship between parent level of knowledge about sexual education for early childhood and their preventive behavior against sexual violence at TK Negeri Pembina Sukamulia. Method: This study used an analytric correlational design with a cross sectional approach. The sampel consisted of all parents of students at TK negeri Pembina Sukamulia, totaling 60 respondents, selected by total sampling. Data were collected using questionnaires on parent knowledge (12 items) dan preventive behavior (14 items). The majority of respondents has good knowledge about sexual education (65%), followed by fair (20%) and moderate (15%) knowledge level. Most parents also demonstrated good preventive behavior against sexual violence. Result: Statistical analysis showed significant relationship between parents’ knowledge level and ther preventive behavior toward sexual violence in early childhood (p value < 0,05). Result: Most respondents had a good level of knowledge about sexual education (64.6%), sufficient (20.3%), and moderate (15.2%). The majority also had good behavior in preventing sexual violence. The test results showed a significant relationship between the level of parental knowledge about sexual education and behavior in preventing sexual violence in early childhood (p-value <0.05). Conclution: There is a significant relationship between parent knowledge level and ther preventive behavior against sexual violence. This is study is expected to serve as a reference for schools, health workers dan cominities to enhance education on sexual education for young children as an effort to protect them from sexual violence.